Fiber Optic Ribbons and Cables
By adding inorganic oxide particles to the tape resin of the optical fiber tape, Young's modulus and surface lubricity are improved, and the problem of increased transmission loss when the optical fiber tape is improved is solved, and the high side pressure characteristics and low transmission loss are achieved.
Patent Information
- Application Number
- CN202080051300.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-07-26
- Filing Date
- 2020-06-04
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2040-06-04
AI Technical Summary
When the existing optical fiber tape core wire improves the side pressure characteristics, the transmission loss is easily increased, making it difficult to achieve high side pressure characteristics and low transmission loss at the same time.
By adding inorganic oxide particles to the tape resin, Young's modulus is improved and the surface lubricity is enhanced, thereby suppressing the increase in transmission loss.
It is achieved to suppress the increase in transmission loss under high side pressure characteristics, ensuring that the loss of the optical fiber tape is difficult to increase during high density accommodation and sharp bending.
Smart Images

Figure CN114127605B_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to optical fiber ribbons and optical fiber cables. This patent application claims priority based on Japanese Patent Application No. 2019-137900 filed on July 26, 2019, and cites all the contents described in the Japanese patent application. Background Art
[0002] There is known an optical fiber ribbon core wire in which a plurality of optical fibers are arranged in parallel and integrated with an overall coating layer (for example, Patent Document 1). The overall coating layer is formed of an ultraviolet curable resin.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Laid-Open No. 05-019150 Summary of the invention
[0006] An optical fiber ribbon according to one embodiment of the present disclosure is an optical fiber ribbon in which a plurality of optical fibers are coated with a ribbon resin, wherein the ribbon resin is a cured product of a resin composition including a base resin and inorganic oxide particles, wherein the base resin contains an oligomer, a monomer, and a photopolymerization initiator. BRIEF DESCRIPTION OF THE DRAWINGS
[0007] [ Figure 1 ] Figure 1 is a schematic cross-sectional view showing an example of an optical fiber.
[0008] [ Figure 2 ] Figure 2 This is a schematic cross-sectional view showing an optical fiber ribbon according to one embodiment. DETAILED DESCRIPTION
[0009] [Problems to be Solved by the Present Disclosure]
[0010] In order to further improve the lateral pressure characteristics of the optical fiber ribbon core wire, it is possible to consider increasing the Young's modulus of the overall coating layer. However, when the Young's modulus is increased by, for example, adjusting the molecular weight of the oligomer of the base resin or the ratio of the mixture, the curing strain applied to the optical fiber may also increase as the Young's modulus increases. Due to this curing strain, the transmission loss of the ribbon core wire tends to increase.
[0011] The present disclosure has been made in view of the above circumstances, and an object of the present disclosure is to provide an optical fiber ribbon capable of suppressing an increase in transmission loss while achieving high lateral pressure characteristics.
[0012] [Effects of the present disclosure]
[0013] According to the present disclosure, it is possible to provide an optical fiber ribbon capable of suppressing an increase in transmission loss while achieving high lateral pressure characteristics.
[0014] [Description of Embodiments of the Present Disclosure]
[0015] First, the contents of the embodiments of the present disclosure are listed and described.
[0016] The optical fiber ribbon involved in one embodiment of the present disclosure is an optical fiber ribbon formed by coating a plurality of optical fibers with a ribbon resin, wherein the ribbon resin is a cured product of a resin composition containing a base resin and inorganic oxide particles, wherein the base resin contains an oligomer, a monomer, and a photopolymerization initiator. According to such an optical fiber ribbon, it is possible to suppress the increase in transmission loss while achieving high lateral pressure characteristics. By including inorganic oxide particles in the ribbon resin, the Young's modulus can be increased without increasing the curing strain. In addition, due to the inorganic oxide particles, the lubricity of the surface of the optical fiber ribbon is improved, thereby suppressing the adhesion between the ribbons. It is believed that this is because the surface of the ribbon is formed with tiny concave-convex shapes formed by inorganic oxide particles. In addition, due to the inclusion of inorganic substances, the surface hardness can be increased compared to the case where the same degree of Young's modulus is obtained using only organic substances. Through these effects, it is believed that it becomes an optical fiber ribbon that is difficult to increase loss even when it is cabled. The optical fiber ribbon involved in this embodiment can be bent sharply when it is stored at a high density. For example, even when using optical fibers with a diameter of φ200 or less, which are considered to have low lateral pressure characteristics, it is possible to suppress the increase in transmission loss when winding on a drum or when it is cabled.
[0017] In one embodiment, the inorganic oxide particles may be particles containing at least one selected from the group consisting of silicon dioxide, zirconium dioxide, aluminum oxide, magnesium oxide, titanium oxide, tin oxide, and zinc oxide. These particles have excellent dispersibility in the resin composition and can easily adjust the Young's modulus.
[0018] In one embodiment, the inorganic oxide particles may be hydrophobic. Inorganic oxide particles into which a hydrophobic group is introduced have excellent dispersibility in a resin composition.
[0019] In one embodiment, the content of the inorganic oxide particles may be 1% by mass or more and 45% by mass or less based on the total amount of the tape resin.
[0020] In one embodiment, the average primary particle size of the inorganic oxide particles may be 650 nm or less.
[0021] In one embodiment, the resin composition may further contain a lubricant.
[0022] In one embodiment, the Young's modulus of the tape resin may be 1100 MPa to 2500 MPa at 23°C.
[0023] An optical fiber ribbon according to one embodiment of the present disclosure is an optical fiber ribbon in which a plurality of optical fibers are coated with a ribbon resin, the ribbon resin containing inorganic oxide particles, and the Young's modulus of the ribbon resin is 1100 MPa to 2500 MPa at 23° C. According to such an optical fiber ribbon, it is possible to suppress an increase in transmission loss while achieving high lateral pressure characteristics.
[0024] In one embodiment, the belt resin may further contain a lubricant.
[0025] An optical fiber cable according to one embodiment of the present disclosure is formed by accommodating the optical fiber ribbon described above in the cable. The optical fiber cable including the optical fiber ribbon described above can also have both high lateral pressure characteristics and low transmission loss.
[0026] [Detailed description of embodiments of the present disclosure]
[0027] Specific examples of optical fiber ribbons and optical fiber cables involved in the embodiments of the present disclosure are described with reference to the accompanying drawings as needed. It should be noted that the present disclosure is not limited to these examples, but is represented by the claims, and is intended to include all changes within the meaning and scope equivalent to the claims. In the following description, the same elements in the description of the drawings are marked with the same symbols, and repeated descriptions are omitted.
[0028] <Optical Fiber Ribbon>
[0029] Optical fiber ribbons are made by coating multiple optical fibers with a ribbon resin.
[0030] (Resin for tape)
[0031] The tape resin (bonding resin) may be a cured product of a resin composition containing a base resin and inorganic oxide particles. The base resin contains an oligomer, a monomer, and a photopolymerization initiator.
[0032] The oligomer preferably contains a carbamate (meth) acrylate oligomer. As the carbamate (meth) acrylate oligomer, an oligomer obtained by reacting a polyol compound, a polyisocyanate compound, and a hydroxyl-containing (meth) acrylate compound can be used. Here, the so-called (meth) acrylate refers to an acrylate or a methacrylate corresponding thereto. This also applies to (meth) acrylic acid.
[0033] Examples of the polyol compound include polytetramethylene glycol, polypropylene glycol, and bisphenol A-ethylene oxide addition diol. Examples of the polyisocyanate compound include 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, isophorone diisocyanate, and dicyclohexylmethane 4,4'-diisocyanate. Examples of the hydroxyl-containing (meth)acrylate compound include 2-hydroxyethyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 1,6-hexanediol mono(meth)acrylate, pentaerythritol tri(meth)acrylate, 2-hydroxypropyl (meth)acrylate, and tripropylene glycol di(meth)acrylate.
[0034] From the viewpoint of adjusting the Young's modulus of the cured product, the number average molecular weight (Mn) of the polyol compound may be 300 or more and 3,000 or less.
[0035] As a catalyst for synthesizing urethane (meth) acrylate oligomers, an organic tin compound is generally used. Examples of the organic tin compound include dibutyltin dilaurate, dibutyltin diacetate, dibutyltin maleate, dibutyltin bis(2-ethylhexyl thioglycolate), dibutyltin bis(isooctyl thioglycolate), and dibutyltin oxide. From the perspective of availability or catalytic performance, dibutyltin dilaurate or dibutyltin diacetate is preferably used as the catalyst.
[0036] When synthesizing the urethane (meth)acrylate oligomer, a lower alcohol having a carbon number of 5 or less may be used. Examples of the lower alcohol include methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 2-butanol, 2-methyl-2-propanol, 1-pentanol, 2-pentanol, 3-pentanol, 2-methyl-1-butanol, 3-methyl-1-butanol, 2-methyl-2-butanol, 3-methyl-2-butanol, and 2,2-dimethyl-1-propanol.
[0037] The oligomer may further contain an epoxy (meth)acrylate oligomer. As the epoxy (meth)acrylate oligomer, an oligomer obtained by reacting a compound having a (meth)acryloyl group with an epoxy resin having two or more glycidyl groups can be used.
[0038] As the monomer, a monofunctional monomer having one polymerizable group and a polyfunctional monomer having two or more polymerizable groups can be used. Two or more monomers can also be used in combination.
[0039] Examples of the monofunctional monomer include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, isobutyl (meth)acrylate, n-pentyl (meth)acrylate, isopentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, isopentyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, isodecyl (meth)acrylate, lauryl (meth)acrylate, 2-phenoxyethyl (meth)acrylate, 3-phenoxyethyl (meth)acrylate, and 1,2-dimethylformamide. (Meth)acrylate monomers such as benzyl acrylate, phenoxydiethylene glycol acrylate, phenoxypolyethylene glycol acrylate, 4-tert-butyl cyclohexanol acrylate, tetrahydrofurfuryl (meth)acrylate, benzyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, dicyclopentyl (meth)acrylate, nonylphenol polyethylene glycol (meth)acrylate, nonylphenol EO modified acrylate, nonylphenoxypolyethylene glycol (meth)acrylate, isobornyl (meth)acrylate, etc.; (meth)acrylic acid, (meth)acrylic acid dimer, carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, ω-carboxy-poly Monomers containing carboxyl groups, such as caprolactone (meth)acrylate; (meth)acrylates containing heterocyclic rings, such as N-acryloylmorpholine, N-vinylpyrrolidone, N-vinylcaprolactam, N-acryloylpiperidine, N-methacryloylpiperidine, N-acryloylpyrrolidine, 3-(3-pyridyl)propyl (meth)acrylate, and cyclotrimethylolpropane formal acrylate; maleimide monomers, such as maleimide, N-cyclohexylmaleimide, and N-phenylmaleimide; (meth)acrylamide, N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N-hexyl(meth)acrylamide, and N-methyl(meth)acrylamide. N-substituted amide monomers such as acrylamide, N-butyl (meth)acrylamide, N-butyl (meth)acrylamide, N-methylol (meth)acrylamide, and N-methylolpropane (meth)acrylamide; aminoalkyl (meth)acrylate monomers such as aminoethyl (meth)acrylate, aminopropyl (meth)acrylate, N,N-dimethylaminoethyl (meth)acrylate, and tert-butylaminoethyl (meth)acrylate; succinimide monomers such as N-(meth)acryloyloxymethylenesuccinimide, N-(meth)acryloyl-6-oxyhexamethylenesuccinimide, and N-(meth)acryloyl-8-oxyoctamethylenesuccinimide.
[0040] Examples of the polyfunctional monomer include ethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, di(meth)acrylate of an alkylene oxide adduct of bisphenol A, tetraethylene glycol di(meth)acrylate, hydroxypivalic acid neopentyl glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,12-dodecanediol di(meth)acrylate, 1,14-tetradecanediol di(meth)acrylate, 1,16-hexadecanediol di(meth)acrylate, 1,20-eicosandiol di(meth)acrylate, isoprene glycol di(meth)acrylate, and 3-ethyl-1,8-octanediol. di(meth)acrylate, EO adduct di(meth)acrylate of bisphenol A, trimethylolpropane tri(meth)acrylate, trimethyloloctane tri(meth)acrylate, trimethylolpropane polyethoxy tri(meth)acrylate, trimethylolpropane polypropoxy tri(meth)acrylate, trimethylolpropane polyethoxy polypropoxy tri(meth)acrylate, tri[(meth)acryloyloxyethyl]isocyanurate, pentaerythritol tri(meth)acrylate, pentaerythritol polyethoxy tetra(meth)acrylate, pentaerythritol polypropoxy tetra(meth)acrylate, pentaerythritol tetra(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate and caprolactone-modified tri[(meth)acryloyloxyethyl]isocyanurate.
[0041] As a photopolymerization initiator, it can be appropriately selected from known free radical photopolymerization initiators and used. As a photopolymerization initiator, for example, 1-hydroxycyclohexyl phenyl ketone (Omnirad 184, manufactured by IGM Resins), 2,2-dimethoxy-2-phenylacetophenone, 1-(4-isopropylphenyl)-2-hydroxy-2-methylpropane-1-one, bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinyl-propane-1-one (Omnirad 907, manufactured by IGM Resins), 2,4,6-trimethylbenzoyldiphenylphosphine oxide (Omnirad TPO, manufactured by IGM Resins) and bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide (Omnirad 819, manufactured by IGM Resins).
[0042] The resin composition may further contain a silane coupling agent, a leveling agent, a defoaming agent, an antioxidant, a sensitizer, a lubricant, and the like.
[0043] The silane coupling agent is not particularly limited as long as it does not hinder the curing of the resin composition. Examples of the silane coupling agent include tetramethyl silicate, tetraethyl silicate, mercaptopropyl trimethoxysilane, vinyl trichlorosilane, vinyl triethoxysilane, vinyl tri(β-methoxy-ethoxy)silane, β-(3,4-epoxycyclohexyl)-ethyl trimethoxysilane, dimethoxydimethylsilane, diethoxydimethylsilane, 3-acryloxypropyl trimethoxysilane, γ-glycidoxypropyl trimethoxysilane, γ-glycidoxypropyl methyl diethoxysilane, γ-methacryloxypropyl trimethoxysilane, N-(β-aminoethyl)silane, and the like.
[0047] The invention also includes the following:
[0048] N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethyldimethoxysilane, N-phenyl-γ-aminopropyltrimethoxysilane, γ-chloropropyltrimethoxysilane, γ-mercaptopropyltrimethoxysilane, γ-aminopropyltrimethoxysilane, bis-[3-(triethoxysilyl)propyl]tetrasulfide, bis-[3-(triethoxysilyl)propyl]disulfide, γ-trimethoxysilylpropyldimethylthiocarbamoyltetrasulfide and γ-trimethoxysilylpropylbenzothiazolyltetrasulfide.
[0044] As a lubricant, for example, silicone oil can be used. The silicone oil is preferably a high molecular weight silicone oil or a modified silicone oil in which a part of the dimethylsiloxane skeleton is modified into an organic group, which is not easy to precipitate on the surface over time. As modified silicone oils, silicone oils that have been modified by polyether, amine, epoxy, mercapto, (meth) acrylic acid, carboxyl, etc. can be listed. By containing a lubricant, adhesion between the belts can be further suppressed, so that a belt whose loss is unlikely to increase when it is cabled can be obtained.
[0045] The viscosity of the resin composition is preferably 300 mPa·s to 3500 mPa·s at 45°C, more preferably 300 mPa·s to 2500 mPa·s, and further preferably 300 mPa·s to 2000 mPa·s. When the viscosity of the resin composition is too high, the coating property is easily reduced. On the other hand, when the viscosity of the resin composition is too low, uneven thickness is likely to occur. In addition, the resin composition can be used as a coating material for optical fibers described later, but in this case, when the viscosity of the resin composition is too high, the coating property is reduced, the coating diameter is unstable when the resin layer is formed, and the optical fiber is prone to breakage. On the other hand, when the viscosity of the resin composition is too low, the self-alignment force is difficult to exert, and uneven thickness is likely to occur.
[0046] (Inorganic oxide particles)
[0047] The inorganic oxide particles are not particularly limited, but from the viewpoint of excellent dispersibility in the resin composition and easy adjustment of the Young's modulus, the inorganic oxide particles are preferably particles containing at least one selected from the group consisting of silica, zirconium dioxide, aluminum oxide, magnesium oxide, titanium oxide, tin oxide, and zinc oxide. From the viewpoints of low price, easy surface treatment, ultraviolet transmittance, and easy impartment of appropriate hardness to the cured product, silica particles are more preferably used as the inorganic oxide particles.
[0048] The inorganic oxide particles are preferably hydrophobic. Specifically, it is preferred that the surface of the inorganic oxide particles is hydrophobically treated by a silane compound. The hydrophobic treatment here refers to the introduction of hydrophobic groups on the surface of the inorganic oxide particles. The inorganic oxide particles into which the hydrophobic groups are introduced have excellent dispersibility in the resin composition. As the hydrophobic group, it can be a reactive group that is UV-curable, such as (meth)acryloyl, vinyl, or a non-reactive group such as a hydrocarbon group (e.g., an alkyl group) or an aryl group (e.g., a phenyl group). When the inorganic oxide particles have reactive groups, it is easy to form a resin layer with a high Young's modulus.
[0049] Examples of the silane compound having a reactive group include silane compounds such as 3-methacryloxypropyltrimethoxysilane, 3-acryloxypropyltrimethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-acryloxypropyltriethoxysilane, 8-methacryloxyoctyltrimethoxysilane, 8-acryloxyoctyltrimethoxysilane, 7-octenyltrimethoxysilane, vinyltrimethoxysilane, and vinyltriethoxysilane.
[0050] Examples of the silane compound having an alkyl group include methyltrimethoxysilane, dimethyldimethoxysilane, ethyltrimethoxysilane, propyltrimethoxysilane, butyltrimethoxysilane, pentyltrimethoxysilane, hexyltrimethoxysilane, octyltrimethoxysilane, methyltriethoxysilane, dimethyldiethoxysilane, ethyltriethoxysilane, propyltriethoxysilane, butyltriethoxysilane, pentyltriethoxysilane, hexyltriethoxysilane, and octyltriethoxysilane.
[0051] When the inorganic oxide particles are added to the resin composition, they can be dispersed in a dispersion medium. By using the inorganic oxide particles dispersed in the dispersion medium, the inorganic oxide particles can be uniformly dispersed in the resin composition, thereby improving the storage stability of the resin composition. As a dispersion medium, as long as it does not hinder the curing of the resin composition, it is not particularly limited. The dispersion medium can be reactive or non-reactive.
[0052] As a reactive dispersion medium, monomers such as (meth)acryloyl compounds and epoxy compounds can be used. Examples of (meth)acryloyl compounds include: 1,6-hexanediol di(meth)acrylate, EO-modified bisphenol A di(meth)acrylate, polyethylene glycol di(meth)acrylate, PO-modified bisphenol A di(meth)acrylate, polypropylene glycol di(meth)acrylate, polytetramethylene glycol di(meth)acrylate, 2-hydroxy-3-phenoxypropyl acrylate, (meth)acrylic acid adducts of propylene glycol diglycidyl ether, (meth)acrylic acid adducts of tripropylene glycol diglycidyl ether, and (meth)acrylic acid adducts of glycerol diglycidyl ether. As a dispersion medium, (meth)acryloyl compounds exemplified in the monomers described later can also be used.
[0053] As a non-reactive dispersion medium, a ketone solvent such as methyl ethyl ketone (MEK) or methyl isobutyl ketone (MIBK); an alcohol solvent such as methanol (MeOH) or propylene glycol monomethyl ether (PGME); or an ester solvent such as propylene glycol monomethyl ether acetate (PGMEA) can be used. When a non-reactive dispersion medium is used, after mixing the base resin and the inorganic oxide particles dispersed in the dispersion medium, a portion of the dispersion medium can be removed to prepare a resin composition.
[0054] From the viewpoint of excellent dispersibility in the resin composition, the average primary particle size of the inorganic oxide particles can be less than 650nm, preferably less than 600nm, more preferably less than 500nm, and further preferably less than 400nm. From the viewpoint of excellent strength after curing, the average primary particle size of the inorganic oxide particles is preferably more than 5nm, more preferably more than 10nm. The average primary particle size can be measured, for example, by image analysis, light scattering, BET method, etc. of electron microscope photographs. In the case where the particle size of the primary particles is relatively small, the dispersion medium of the primary particles of the inorganic oxide particles appears to be transparent under visual observation. In the case where the particle size of the primary particles is relatively large (more than 40nm), the dispersion medium of the primary particles appears to be turbid, but no precipitate is observed.
[0055] Based on the total amount of the resin composition (the total amount of the base resin and the inorganic oxide particles), the content of the inorganic oxide particles can be 1% by mass or more and 45% by mass or less, preferably 2% by mass or more and 40% by mass or less, and more preferably 3% by mass or more and 35% by mass or less. When the content of the inorganic oxide particles is 1% by mass or more, a tough cured product is easily formed. When the content of the inorganic oxide particles is 45% by mass or less, a cured product in which the inorganic oxide particles are well dispersed is easily formed. Since the total amount of the resin composition is substantially the same as the total amount of the cured product of the resin composition, the provisions of the content of the above-mentioned inorganic oxide particles can also be applied to the total amount of the tape resin.
[0056] The Young's modulus of the tape resin may be 1100 MPa to 2500 MPa at 23° C., but is preferably 1100 MPa to 2000 MPa, and more preferably 1400 MPa to 2000 MPa. When the Young's modulus of the tape resin is 1100 MPa or more, the lateral pressure characteristics are easily improved, and when it is 2500 MPa or less, appropriate toughness can be imparted to the tape resin, so that cracks are less likely to occur in the tape resin.
[0057] (optical fiber)
[0058] Figure 1 The optical fiber 10 includes a glass fiber 13 including a core 11 and a cladding 12 , and a coating resin layer 16 provided on the periphery of the glass fiber 13 and including a primary resin layer 14 and a secondary resin layer 15 .
[0059] The cladding 12 surrounds the core 11. The core 11 and the cladding 12 mainly include glass such as quartz glass. For example, the core 11 can use quartz glass doped with germanium or pure quartz glass, and the cladding 12 can use pure quartz glass or quartz glass doped with fluorine.
[0060] exist Figure 1 For example, the outer diameter (D2) of the glass fiber 13 is about 100 μm to about 125 μm, and the diameter (D1) of the core 11 constituting the glass fiber 13 is about 7 μm to about 15 μm. The thickness of the coating resin layer 16 is usually about 22 μm to about 70 μm. The thickness of each layer of the primary resin layer 14 and the secondary resin layer 15 can be about 5 μm to about 50 μm.
[0061] When the outer diameter (D2) of the glass fiber 13 is about 125 μm and the thickness of the coating resin layer 16 is 60 μm to 70 μm, the thickness of each layer of the primary resin layer 14 and the secondary resin layer 15 can be about 10 μm to 50 μm, for example, the thickness of the primary resin layer 14 can be 35 μm, and the thickness of the secondary resin layer 15 can be 25 μm. The outer diameter of the optical fiber 10 can be about 245 μm to 265 μm.
[0062] When the outer diameter (D2) of the glass fiber 13 is about 125 μm and the thickness of the coating resin layer 16 is 27 μm to 48 μm, the thickness of each layer of the primary resin layer 14 and the secondary resin layer 15 can be about 10 μm to 38 μm, for example, the thickness of the primary resin layer 14 can be 25 μm, and the thickness of the secondary resin layer 15 can be 10 μm. The outer diameter of the optical fiber 10 can be about 179 μm to 221 μm.
[0063] When the outer diameter (D2) of the glass fiber 13 is about 100 μm and the thickness of the coating resin layer 16 is 22 μm to 37 μm, the thickness of each layer of the primary resin layer 14 and the secondary resin layer 15 can be about 5 μm to 32 μm, for example, the thickness of the primary resin layer 14 can be 25 μm, and the thickness of the secondary resin layer 15 can be 10 μm. The outer diameter of the optical fiber 10 can be about 144 μm to 174 μm.
[0064] The resin composition for forming the tape resin is suitable for the secondary resin layer. The secondary resin layer can be formed by curing the resin composition containing the inorganic oxide particles and the base resin. Thus, the lateral pressure characteristics of the optical fiber can be improved.
[0065] The method for producing an optical fiber comprises: a coating step of coating the resin composition on the outer circumference of a glass fiber composed of a core and a cladding; and a curing step of curing the resin composition by irradiating ultraviolet rays after the coating step.
[0066] The Young's modulus of the secondary resin layer is preferably 1300 MPa or more, more preferably 1300 MPa or more and 3600 MPa or less, and further preferably 1400 MPa or more and 3000 MPa or less at 23° C. When the Young's modulus of the secondary resin layer is 1300 MPa or more, the lateral pressure characteristics are easily improved, and when it is 3600 MPa or less, appropriate toughness can be imparted to the secondary resin layer, so that cracks are less likely to occur in the secondary resin layer.
[0067] The primary resin layer 14 can be formed, for example, by curing a resin composition containing a urethane (meth) acrylate oligomer, a monomer, a photopolymerization initiator, and a silane coupling agent. The resin composition for the primary resin layer can use a conventionally known technique. As the urethane (meth) acrylate oligomer, the monomer, the photopolymerization initiator, and the silane coupling agent, the compounds exemplified in the above-mentioned base resin can be appropriately selected. However, the resin composition forming the primary resin layer has a different composition from the base resin forming the secondary resin layer.
[0068] Figure 2 1 is a schematic cross-sectional view showing an optical fiber ribbon according to one embodiment. As described above, the optical fiber ribbon 100 is formed by coating a plurality of optical fibers 10 with a ribbon resin 40 (integrally). Figure 2 In FIG. 4 , four optical fibers 10 are shown as an example, but the number is not particularly limited.
[0069] The optical fibers 10 may be integrated in a state of being adjacent and arranged side by side, or a part or all of the optical fibers 10 may be integrated in a state of being spaced apart and arranged side by side at a certain interval. However, the center-to-center distance F between adjacent optical fibers 10 is preferably 250±30 μm or less. When the center-to-center distance is set to 250 μm, it is easy to place the optical fibers on the existing V-grooves, thereby obtaining an optical fiber ribbon with excellent overall fusion properties.
[0070] The thickness T of the optical fiber ribbon 100 also depends on the diameter of the optical fiber 10, but is preferably 164 μm to 285 μm. When the optical fibers 10 are spaced apart and arranged side by side at a certain interval, that is, when adjacent optical fibers 10 are joined via the ribbon resin 40 without contact, the thickness of the ribbon resin at the center between the optical fibers 10 can be set to 20 μm to 40 μm.
[0071] <Optical Fiber Cable>
[0072] The optical fiber cable is formed by accommodating the optical fiber ribbon in the cable. As the optical fiber cable, for example, a slit-type optical fiber cable having a plurality of slit grooves can be cited. The optical fiber ribbon is installed in the slit grooves in such a manner that the installation density in each slit groove is about 25% to 65%. The installation density refers to the ratio of the cross-sectional area of the optical fiber ribbon installed in the slit groove to the cross-sectional area of the slit groove.
[0073] Example
[0074] Hereinafter, the present disclosure will be described in more detail by showing the evaluation test results using the examples and comparative examples related to the present disclosure. It should be noted that the present disclosure is not limited to these examples.
[0075] [Resin composition for forming tape resin]
[0076] (Oligomer)
[0077] As the oligomer, a urethane acrylate oligomer obtained by reacting polypropylene glycol having a molecular weight of 1000, 2,4-toluene diisocyanate, and 2-hydroxyethyl acrylate was prepared.
[0078] (monomer)
[0079] As monomers, 2-phenoxyethyl acrylate, tripropylene glycol diacrylate, and N-vinyl caprolactam were prepared.
[0080] (Photopolymerization Initiator)
[0081] As a photopolymerization initiator, 1-hydroxycyclohexyl phenyl ketone and 2,4,6-trimethylbenzoyldiphenylphosphine oxide were prepared.
[0082] (Inorganic oxide particles)
[0083] As inorganic oxide particles, hydrophobic silica particles with an average primary particle size of 10 nm to 15 nm, hydrophobic silica particles with an average primary particle size of 70 nm to 100 nm, and hydrophobic silica particles with an average primary particle size of 250 nm to 350 nm were prepared. These silica particles have a methacryloyl group and are dispersed in methyl ethyl ketone (MEK).
[0084] A base resin was prepared by mixing 70 parts by mass of urethane acrylate oligomer, 10 parts by mass of 2-phenoxyethyl acrylate, 13 parts by mass of tripropylene glycol diacrylate, 5 parts by mass of N-vinyl caprolactam, 1 part by mass of 1-hydroxycyclohexyl phenyl ketone, and 1 part by mass of 2,4,6-trimethylbenzoyldiphenylphosphine oxide.
[0085] Next, after mixing each silica sol with a base resin, most of the MEK as a dispersion medium was removed under reduced pressure, and the resin compositions of Examples and Comparative Examples (resin compositions for forming belt resins) were prepared in such a manner that the contents of silica particles were as shown in Table 1. It should be noted that in Example 7, silicone oil as a lubricant was added to the resin composition in the amount shown in Table 1.
[0086] [Table 1]
[0087]
[0088] [Resin composition for secondary resin layer]
[0089] A resin composition for a secondary resin layer was prepared by mixing 60 parts by mass of a urethane acrylate oligomer which is a reaction product of polypropylene glycol having a molecular weight of 1000, isophorone diisocyanate and 2-hydroxyethyl acrylate, 19 parts by mass of isobornyl acrylate, 20 parts by mass of trimethylolpropane triacrylate, and 1 part by mass of 2,4,6-trimethylbenzoyldiphenylphosphine oxide.
[0090] [Resin composition for primary resin layer]
[0091] A resin composition for a primary resin layer was prepared by mixing 75 parts by mass of a urethane acrylate oligomer which is a reaction product of polypropylene glycol having a molecular weight of 2000, 2,4-toluene diisocyanate, 2-hydroxyethyl acrylate and methanol, 12 parts by mass of nonylphenol EO-modified acrylate, 6 parts by mass of N-vinyl caprolactam, 2 parts by mass of 1,6-hexanediol diacrylate, 1 part by mass of 2,4,6-trimethylbenzoyldiphenylphosphine oxide, and 1 part by mass of γ-mercaptopropyltrimethoxysilane.
[0092] [Production of optical fiber]
[0093] The resin composition for the primary resin layer and the resin composition for the secondary resin layer were applied to the outer periphery of a glass fiber having a diameter of 125 μm consisting of a core and a cladding, and then the resin composition was cured by irradiating ultraviolet rays to form a primary resin layer having a thickness of 20 μm and a secondary resin layer having a thickness of 17.5 μm on the outer periphery thereof, thereby producing an optical fiber having a diameter of 200 μm. The line speed was set to 150 m / min.
[0094] [Fabrication of optical fiber ribbon]
[0095] The resin composition for forming the tape resin is applied to the outer periphery of the four adjacent and parallel optical fibers, and then the resin composition is cured by irradiating with ultraviolet light. Figure 2 The thickness T) of the optical fiber ribbon shown is 230 μm. The line speed during the curing of the resin composition was set to 500 m / min.
[0096] [Production of optical fiber cables]
[0097] A slit-type optical fiber cable having six slit slots was prepared. The optical fiber ribbon was installed in the slit slots so that the installation density in each slit slot was 50%. The installation density refers to the ratio of the cross-sectional area of the optical fiber ribbon installed in the slit slot to the cross-sectional area of the slit slot.
[0098] [Various reviews]
[0099] The following evaluations were performed using the resin compositions for forming ribbons and the optical fiber ribbons obtained in the examples and comparative examples.
[0100] (Young's modulus)
[0101] The resin composition was applied onto a polyethylene terephthalate (PET) film using a spin coater, and then an electrodeless UV lamp system (D valve) (manufactured by Heleus) was used at 1000±100 mJ / cm 2 The resin layer was cured under the conditions of . Thus, a resin layer with a thickness of 200±20 μm was formed on the PET film. The resin layer was peeled off from the PET film to obtain a resin film.
[0102] The resin film was punched into a dumbbell shape of JIS K 7127 Type 5 as an evaluation sample. The evaluation sample was stretched using a tensile tester at a stretching speed of 1 mm / min and a line spacing of 25 mm under the conditions of 23±2°C and 50±10% RH to obtain a stress-strain curve. The Young's modulus was then obtained from the 2.5% tangent line.
[0103] (Cable loss characteristics)
[0104] The optical fiber ribbon was left to stand in a low temperature (-40°C) environment, and the transmission loss value when the wavelength of the signal light was 1.55 μm was measured. The measured value was evaluated according to the following criteria.
[0105] A: Transmission loss is less than 0.3dB / km.
[0106] B: Transmission loss exceeds 0.3dB / km and is less than 0.5dB / km.
[0107] C: Transmission loss exceeds 0.5dB / km.
[0108] [Table 2]
[0109]
[0110] The optical fiber ribbon of the embodiment has excellent lateral pressure characteristics and can suppress an increase in transmission loss.
[0111] Explanation of symbols
[0112] 10. Fiber Optics
[0113] 11 Core
[0114] 12 Cladding
[0115] 13 Fiberglass
[0116] 14 Primary resin layer
[0117] 15 Secondary resin layer
[0118] 16 Coating resin layer
[0119] 40 Belt Resin
[0120] 100 Fiber Optic Ribbon
Claims
1. An optical fiber ribbon, which is formed by coating a plurality of optical fibers with a ribbon resin, The tape resin is a cured product of a resin composition comprising a base resin and inorganic oxide particles, wherein the base resin contains an oligomer, a monomer, and a photopolymerization initiator. The inorganic oxide particles are silicon dioxide particles, The inorganic oxide particles are hydrophobic, and (meth)acryloyl groups as hydrophobic groups are introduced on the surface of the particles.
2. The optical fiber ribbon according to claim 1, wherein: The content of the inorganic oxide particles is 1 mass % or more and 45 mass % or less based on the total amount of the tape resin.
3. The optical fiber ribbon according to claim 1 or claim 2, wherein: The average primary particle size of the inorganic oxide particles is 650 nm or less.
4. The optical fiber ribbon according to claim 1 or claim 2, wherein: The resin composition further contains a lubricant.
5. The optical fiber ribbon according to claim 1 or claim 2, wherein: The Young's modulus of the tape resin is 1100 MPa to 2500 MPa at 23°C.
6. An optical fiber cable, comprising the optical fiber ribbon according to any one of claims 1 to 5 housed in the cable.
Citation Information
Patent Citations
Coated optical fiber tape and optical cable using the same
JP1993019150A
Method for producing nanoparticles and its use
JP2019137900A
Radiation-Curable Liquid Resin Optical Fiber Upjacket Composition
US20080045623A1
Optical fiber ribbon
US20090052847A1